Research and development management: When used in universities as fundamental to generate and produce knowledge social entities. - Cristina Seijo Suárez (Universidad del Magdalena, 2013)
This article intends, to offer an integral vision of the Management of Investigation and Development: Case of application in universities like social organizations fundamental to generate and to produce knowledge, in a world which every time the knowledge has become a producing strategic tool of science, technology and innovation in the world-wide economy. The present investigation leans in authors like Strap (1996), Romero (2001), Schavino (2003), among others, being made under a interpretative symbolic approach, through a qualitative methodology of descriptive type and non experimental design, by means of a documentary analysis. On the matter the university as generating center of knowledge has the commitment strategic to transform its immediate and mediate surroundings, with the purpose of permanently improving the quality of life of the population, understood this one not only like the satisfaction of the demand of goods and services, but also like the cultural development and the conservation and improvement of environment. In relation to the final considerations, the university must reframe the traditional functions expanding of innovating way to the development of the investigation that demands the scientific development and establishing a solid bridge that ties the scientific activity that it generates with the search of answers that benefit the society.